2022
DOI: 10.3390/coatings12101464
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and Analysis of the Relationship Model between Macro-Texture and Skid Resistance Performance of Asphalt Pavement

Abstract: Pavement surface texture evaluation is mainly analyzed based on elevation data in previous research, and attention also need to be paid to wavelength information. Furthermore, a well-established relationship model between surface texture and skid resistance for real road sections still needs further investigation to help provide useful information on appropriate maintenance time considering skid resistance attenuation. In this research, the macro-texture of asphalt pavement was evaluated from different aspects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Li et al [35] proposed a three-stage calculation of MTDs, and concluded that both the electric-sand-patch method and the 3D laser method have a good correlation with the sand patch method, but the laser method has better repeatability. Jie et al [36] monitored anti-skidding performance and the macrotexture of six road sections for 18 months, the results indicated that the macrotexture indexes calculated based on elevation data to characterize vertical irregularities have a good correlation with the skid resistance. However, none of the above studies can effectively and accurately characterize the inhomogeneous macrotexture of pavements, and there is a lack of long-term testing statistics, and they are difficult to fully and accurately evaluate the deterioration of the micromilled surface skid resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [35] proposed a three-stage calculation of MTDs, and concluded that both the electric-sand-patch method and the 3D laser method have a good correlation with the sand patch method, but the laser method has better repeatability. Jie et al [36] monitored anti-skidding performance and the macrotexture of six road sections for 18 months, the results indicated that the macrotexture indexes calculated based on elevation data to characterize vertical irregularities have a good correlation with the skid resistance. However, none of the above studies can effectively and accurately characterize the inhomogeneous macrotexture of pavements, and there is a lack of long-term testing statistics, and they are difficult to fully and accurately evaluate the deterioration of the micromilled surface skid resistance.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, in recent years, many scholars at home and abroad have carried out extensive research on the surface texture and antiskidding performance of asphalt pavement. For instance, the skid resistance of pavement, especially in wet road conditions on rainy days, is closely related to macro-texture which provides a drainage system for water on the pavement surface, thus preventing a buildup of water between the tire and the pavement and resultant hydroplaning [7][8][9]. In the meantime, researchers believe that the type, apparent morphology and mineral composition of aggregates in the surface layer of pavement play an important role in the formation of surface texture [5,[10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%